Identify the second step in solving this equation for y

: −3(y + 6) = 21
. (1 point)
Responses

Add 6 to both sides.
Add 6 to both sides.

Divide both sides by 6.
Divide both sides by 6.

Divide both sides by −3
.
Divide both sides by negative 3.

Subtract 6 from both sides.

1 answer

To solve the equation \(-3(y + 6) = 21\), the first step is to divide both sides by \(-3\) to isolate the term \((y + 6)\).

The second step after dividing by \(-3\) would be to simplify the equation. Once divided, the equation becomes:

\[ y + 6 = -7 \]

Now, you would proceed to solve for \(y\).

Therefore, the correct response that identifies the second step in solving the equation is:

Divide both sides by −3.

Similar Questions
  1. Solving the equation 6x + 2(x − 1) = 30Given: 6x + 2(x − 1) = 30 Step 1: 6x + 2x − 2 = 30 Step 2: 8x − 2 = 30 Step 3: 8x
    1. answers icon 3 answers
  2. Solving the equation 6x + 2(x − 1) = 30Given: 6x + 2(x − 1) = 30 Step 1: 6x + 2x − 2 = 30 Step 2: 8x − 2 = 30 Step 3: 8x
    1. answers icon 1 answer
    1. answers icon 3 answers
    1. answers icon 1 answer
more similar questions